Spontaneous Severe Haemoperitoneum in the Third Trimester Leading to Intrauterine Death: Case Report - Harriet Williamson; Radha Indusekhar; Alexander Clark; Ismail M. Hassan (Hindawi Limited, 2011)
Spontaneous haemoperitoneum during pregnancy is a rare but potentially catastrophic cause of acute abdominal pain. A healthy 37-year-old primigravida presented with acute abdominal pain and hypovolaemic shock at 37-weeks gestation. An emergency caesarean section was indicated on the clinical suspicion of placental abruption. However, an ultrasound scan confirmed the absence of a fetal heartbeat, and, in light of the mother's haemodynamic stability, a vaginal delivery was deemed most appropriate. Subsequent imaging, due to deterioration over the following 24-hours, revealed a large heterogenous haematoma within the pelvic cavity, which was later found to be caused by severe pelvic endometriosis. Despite fertility problems associated with severe endometriosis, advanced assisted reproductive technology enables more of these patients to become pregnant, highlighting the need to be aware of this rare complication in pregnancy.